Tyler’s Goal-Oriented Approach For The Evaluation Of Leadership Training Implementation - Harahap, Susi Susilawati; Asmawi, Moch.; Wibowo, Wibowo (International Journal of Educational Research & Social Sciences, 2022)
The objective of this study is to evaluate a leadership training program by Tyler’s goal-oriented theory. Tyler’s evaluation is a process to decide whether realization the goal or not. This study was conducted to implement leadership training at Level III (for echelon III or administrator) of government employees held by the human resources development agency of Jakarta in 2005-2008. The data was analyzed by using qualitative analyses. The results found that implementation of leadership training at Level III organized by the Human Resource Development Agency (BPSDM) runs effectively based on its stipulation in Perla No.19/2015. The improvement of visionary leadership competence found that almost all participants who become the sample of this study do projectchange evaluation with the middle period milestone. Tyler’s approach matches leadership-training implementation. Due to applying this approach, the strengths and weaknesses could be seen, starting from the participants, interviewees, curriculum, and evaluation.